Textbook of Emergency Cardiology - Maisel, A. S. Alan S.; Peacock, W. F. W. Frank (Jaypee Brothers Medical Publishers, 2021)
The aim of this textbook is to focus on the emergency cardiology. Cardiology is a medical specialty and a branch of internal medicine concerned with disorders of the heart. This textbook of Emergency Cardiology offers highly practical advice on the diagnosis and management of acute cardiac conditions. Throughout the book the authors employ an evidence-based approach to clinical practice, and provide detailed guidance for day-to-day practice in a wider variety of settings - from the emergency department to intensive care and the cardiac ward. This book is divided into 4 sections that include cardiac arrest, acute myocardial infarction and acute coronary syndrome, acute heart failure, and arrhythmias, which are further divided into 36 chapters. Individual chapters are well written and easy to read. The text of this book is further enhanced by more than 300 clinical photographs, radiological images, tables and figures. This book is a must-read reference book with information that is useful in every day clinical practice for cardiologists.